Ahmad Al-Ghumâri's Contribution to Moroccan Hadith Studies; Study of the Book of Al-Mudâwî Li ʻilal Al-Jâmi’ Al-Saghîr Wa Syarhai Al-Munâwî - Muhammad Mukhlis Arif (UIN Syarif Hidayatullah Jakarta, 2025)
This research aims to examine Ahmad al-Ghumârî contribution to the development of Hadith studies in Morocco through a critical analysis of his work Al-Mudâwî li ʻIlal al-Jâmi' al-Saghîr wa Syarhai al-Munâwî. The main issue addressed is how al-Ghumârî applied his Hadith criticism methodology in evaluating the traditions found in al-Suyûtî's Al-Jâmi' al-Saghîr and its commentary by al-Munâwî. This study employs a content analysis method with a historical-critical approach to the text of Al-Mudâwî. The findings reveal that al-Ghumârî introduced a comprehensive Hadith criticism methodology by combining chain of transmission (sanad) and textual (primary) analysis while providing new assessments of Hadith status that often differed from previous evaluations. Al-Ghumârî's significant contribution lies in his precision in identifying hidden defects ('ilal') in Hadith and his ability to provide strong arguments for determining Hadith status based on strict principles of Hadith science.